Di tutti gli animali selvaggi il più pericoloso è la donna. Perché Ipazia doveva morire - Fulvia Cigala Fulgosi; Enrica De Simoni; Enrica Salvador (Il sogno della farfalla, 2008)
The article proposes to look into the roots of the centuries-old negation and depreciation that women have undergone in Western culture characterized by the Catholic religion. The research dates back to the origins of Christianity and to the elaboration, in the first centuries after Christ, of the prescriptive model of femininity inspired by the belief in original sin. By directly examining a number of sources we are able to see the evolution of the canons dictating the image of the “perfect Christian woman”: from Paul of Tarsus to the Fathers of the Church in the early centuries, to Augustin of Hippo, who played a central role in the codification of women as “enemies of man and God”. From this analysis we are able to learn that the main nucleus of misogyny expressed by the early Christian thinkers, heirs to Greek philosophy, lies in the idea that man is constitutionally split between a rational soul which allows him to relate to God, and the body dominated by uncontrollable irrational impulses, which make him wallow in sin. In this light sexuality becomes absolute Evil and Christian women who want to save their souls, must give up on their sexual identity and submit to the patriarchal laws dictated by God. Rebelling to this castrating command, defending one’s autonomous thinking and liberty of action, requires women to pay a high price. The emblematic figure of Hypatia demonstrates this. A great philosopher and scientist from Alexandria she was barbarically assassinated on the incitement of a powerful and cruel Christian bishop. Her tragic death assumes a highly symbolical value, marking the end of paganism, that agonizes under the ruthless attack of the Catholic church, ally of the declining imperial power. And presaging the destiny of women as minorities and alienated from themselves which the Catholic church will reserve for women over the centuries.